(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
In this paper the development of artificial intelligence (AI) is debated, highlighting the opportunity to avoid misleading narratives and excessive AI anthropomorphization. Furthermore, the impact that AI can have on the constitutional framework and the main areas of the state-citizen relationship is examined. Therefore, the benefits and potential risks related to AI are analysed, having special consideration for new phenomena of algorithmic discrimination. In conclusion, an analysis of the data protection contribution to the fundamental constitutional principles effectiveness in the new digital ecosystem is provided.